4CPS-008 Risk factors associated with readmission to the emergency department in patients with previous gastrointestinal haemorrhage secondary to oral anticoagulant therapy. (24th March 2020) - López Vinardell, L; Ruiz Ramos, J; Juanes Borrego, A; Puig-Campmany, M; Mangues Bafalluy, MA
Abstract : Background and importance: Several studies have analysed the risk factors for admission to the emergency department (ED) due to gastrointestinal haemorrhage (GH) related to oral anticoagulant therapy (OAT). However, the effect of treatment modification at discharge on readmission rates and short term mortality are not known. Aim and objectives: To describe the frequency and risk factors associated with readmission rates to the ED in patients with previous GH secondary to OAT at 30 days and 1 year after discharge and its mortality. Material and methods: This was a retrospective observational study conducted in a tertiary hospital. Adult patients treated with OAT who consulted an ED due to coagulation disorders were included (January 2017–June 2019). Multivariate analysis was designed, including clinical variables, with a value of p<0.2 in a previous univariate analysis. The factors analysed included age, sex, comorbidities (chronic renal failure (CRF), heart failure, diabetes, hypertension, dementia, cirrhosis) and concomitant treatment (AINE, antiplatelet therapy, IBP). Results: Seventy-four patients were included (mean age 83 (62–97) years). Forty-one (55.4%) were treated with vitamin K antagonists (VKA) and 33 (44.6%) with direct oral anticoagulants (DOAC). Initial OAT was changed at discharge in 17 (24.2%) patients to another OAT (4 cases) or to heparin (13 cases). Three of them presented to the ED 30 days after discharge and 6 during the year due to a blood clotting problem. Among the 57 patients with no change in OAT (31 VKA, 26 DOAC), 6 presented again to the ED in the 30 days after discharge and 10 during the year after discharge because of a coagulation disorder. No patient deaths were linked to OAT problem. Multivariate analysis revealed that treatment modification at discharge did not affect readmission rates but being treated with DOACs tended to protect against readmission during the first year after discharge (OR 0.47 (0.15–1.11)). Regarding risk related factors, CRF was the only variable associated with 30 day readmission (OR 3.10 (1.02–9.41)) whereas taking antiplatelet drugs tended to increase the risk of readmission in the first year (OR 2.44 (1.07–8.41)). Conclusion and relevance: DOACs could play a protect role against readmission whereas CRF and antiplatelet therapy tended to increase the risk of readmission at 30 days and in the first year after discharge. However, more data are needed to confirm our results. References and/or acknowledgements: Thank you everyone for the collaboration. No conflict of interest.